KARAKTERISTIK HABITAT DI SARANG TANGKASI (Tarsius Spectrumgurskyae) DI TAMAN HUTAN RAYA GUNUNG TUMPA H.V. WORANG, SULAWESI UTARA - Sahdin Sapsuha; Johny S. Tasirin; Saroyo Sumarto (Universitas Sam Ratulangi, 2021)
ABSTRAK This study aims to determine th characteristics of the habitat in the nest of Tangkasi (Tarsius spectrumgurskyae) in the Gunung Tumpa Forest Park HV Worang. The research was carried out from October to November 2020. In collecting the tangkasi nest data, the observations were divided into three stages, namely: 1. Determination of nests. 2. Observation of nest characteristics and 3. Observation of the condition of the nest environment. This observation was carried out in the afternoon until the evening, namely at 16-30 - 18-30 and at dawn, namely at 04-30-06:00 WITA. The results of the study have obtained the location of the coordinates of the tangkasi nests as many as 8 nests spread over several types of land cover in the Tahura area of Gunung Tumpa HV Worang. The types of nest plants that make up Tarsius spectrumgurskyae are found in the Ficus and Arenga genera. The nest structure consists of cavities in the interweaving of roots and piles of interwoven fibers between the leaf midribs and found 1-6 individual tangkassi in each nest. Tangkasi nests are foundat an elevation of 462-574 m with a slope of 11% - 25%. Environmental conditions around the nest with light intensity 351.6 ± 39.71 lx, light percentage 19.9% ± 1.94%. The morning, afternoon and evening temperatures were 25.74ºC ± 0.42, 30.88 88C ± 0.47 and 25.79 C ± 0.35 with humidity in the morning, afternoon and evening 91.71% ± 2.54%, 77.48% ± 2.80% and 74.31% ± 19.4%. The vegetation of the nest habitat was dominated by Spathodea campanulata (INP 51.32%) for trees, Leucosyke capitellata (INP 27.99%) for poles and calamus sp. (INP 31.68%) for saplings. Keywords: Tangkasi, habitat characteristics, Tangkasi nest, Tahura Gunung Tumpa H.V Worang